Henry and Mudge and the snowman plan : the nineteenth book of their adventures - Rylant, Cynthia (Rylant, Cynthia. Henry and Mudge books., 1999)
Henry, his dog Mudge, and his father enter a snowman building contest at the local park and win third place.